Synthesis of imidazolium hydrogen sulphate and morpholinium tetrafluoroborate ionic liquids: Its antimicrobial activity - Nurul Aliaa, Rahman; Wan Mohd Hafizuddin, Wan Yussof; Wan Salwanis, Md Zain; Suhaila, Omar; Jefri, Jaapar (Trans Tech Publications Ltd., 2022)
Recent years have seen renewed interest in the application of ionic liquids (Ils) on extraction. Along with this grow of ionic liquids, there are significant concern over the effect of ILs on the biomass extraction. Therefore the aim of this present work was to study the inhibitory effect of synthesized ILs particularly imidazolium hydrogen sulphate [IM][HSO4] and morpholinium tetrafluoroborate [MOR][BF4]. Antibaterial and antifungal activities were carried out against Bacillus cereus, Bacillus thuringiensis and Pseudallescheria boydii which are the main producer of ferulic acid (FA). Results showed that the inhibitory effects of [IM][HSO4] againts bacteria (Bacillus cereus and Bacillus thuringiensis) and fungus (Pseudallescheria boydii) were more extensive with inhibition zone of 20.3 and 52.3 mm respectively compared to [MOR][BF4] with 8.3 and 34.0 mm. This result represented the inhibitory effect of ILs especially on fungus as compared to bacteria tested in this present study.